2021
DOI: 10.1136/bmj.n2177
|View full text |Cite
|
Sign up to set email alerts
|

Climate crisis: Over 200 health journals urge world leaders to tackle “catastrophic harm”

Abstract: More than 200 health journals have called on governments to take emergency action to tackle the "catastrophic harm to health" from climate change.A joint editorial says that while recent targets to reduce emissions and conserve biodiversity are welcome, they are not enough and need to be matched with credible short and longer term plans. 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 1 publication
0
21
0
Order By: Relevance
“…The Intergovernmental Panel on Climate Change (IPCC), warned that global warming will significantly affect hundreds of millions of people [ 1 ], but also found that mitigation options are available in every major sector and on every scale, from local to international. The medical scientific community has increasingly urged for emergency action on climate change [ 2 , 3 ]. In this context, The Lancet Countdown on health and climate change started to review annually forty-one indicators that explore the relation between health and climate change and to assess the progress made by governments towards their engagement to the 2015 Paris agreement [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (IPCC), warned that global warming will significantly affect hundreds of millions of people [ 1 ], but also found that mitigation options are available in every major sector and on every scale, from local to international. The medical scientific community has increasingly urged for emergency action on climate change [ 2 , 3 ]. In this context, The Lancet Countdown on health and climate change started to review annually forty-one indicators that explore the relation between health and climate change and to assess the progress made by governments towards their engagement to the 2015 Paris agreement [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…On September 6, 2021, 233 health and clinical medicine journals published an editorial calling on governments to take emergency action to tackle the catastrophic harm to health from climate change [1]. This call was published a decade after the Lancet Commission naming climate change the biggest global health threat of the 21st century [2], and it follows a recent Intergovernmental Panel on Climate Change (IPCC) report that stated that 'it is unequivocal that human influence has warmed the atmosphere, ocean, and land' [3].…”
Section: Introductionmentioning
confidence: 99%
“…Last year the climate crisis was described by more than 200 health journals, in an unprecedented joint editorial,4 as risking “catastrophic harm to health that will be impossible to reverse,” the letter adds.…”
mentioning
confidence: 99%